Analysis of Effect of Education and Training, Compensation and Working Environment on Employee Performance at the District Secretariat Soppeng - Andi Asnani; Mattalatta - (STIE AMKOP, 2016)
ABSTRACT This research aims to: 1) analyze the effect of education and training to on employee performance at the District Secretariat of Soppeng Regency, 2) analyze the effect of compensation on employee performance at the District Secretariat of Soppeng Regency, 3) analyze the effect of the work environment on employee performance at the District Secretariat of Soppeng Regency, 4) analyze the effect of education and training, compensation, and work environment to on employee performance at the District Secretariat of Soppeng Regency. The research location is at the District Secretariat of Soppeng Regenc, South Sulawesi Province. Population in this study were all employees of the District Secretariat of Soppeng Regency which amounted to 152 employees. Sampling in this research is using the Slovin formula, so that the number of samples examined in this study are 61 employees. For testing the hypothesis with multiple regression analysis. The results showed that: 1) education and training has positive and significant effect on employee performance at the District Secretariat of Soppeng Regency, 2) compensation has positive and significant effect on employee performance at the District Secretariat of Soppeng Regency, 3) working environment has positive and significant effect on employee performance at the District Secretariat of Soppeng Regency, 4) education and training, compensation and working environment simultaneously have positive and significant effect on employee performance at the District Secretariat of Soppeng Regency, .Keywords: Education and Training, Compensation, Work Environment, Employee Performance